Chiari I malformation with underlying pseudotumor cerebri: Poor symptom relief following posterior decompression surgery. (2017) - Alnemari, Ahmed; Mansour, Tarek R.; Gregory, Stephanie; Miller, William K.; Buehler, Mark; Gaudin, Daniel
Highlights: Chiari I malformation with underlying pseudotumor cerebri can result in poor outcomes following posterior decompression surgery. Appropriate radiological studies must be performed pre-operatively in order to obtain the correct diagnosis in cases with clinical symptoms that could be suggestive of either PTC or CMI. Further research is crucial for generating a standardized set of data to help medical teams determine a patient's probability for coexistence of PTC and CMI. Abstract: Introduction: Pseudotumor cerebri (PTC) patients exhibit clear clinical signs and symptoms of higher intracranial pressure (ICP) without ventricular enlargement or mass lesions. The clinical picture of patients with PTC can sometimes be similar to that of Chiari Malformation type I (CMI). There is some evidence that Chiari I malformation and PTC may coexist, which raises the question of whether PTC is an idiopathic disease or a complication of posterior decompression surgery—treatment of choice for Chiari I malformation. Presentation of cases: A retrospective review of electronic medical records of patients diagnosed with PTC at the University of Toledo Medical Center (UTMC) was performed. The objective was to determine whether PTC patients had a concurrent diagnosis of Chiari I malformation and whether the diagnosis of PTC occurred before or after posterior decompression surgery. Out of the 8 eligible patient medical records reviewed, 5 patients diagnosed with PTC had undergone posterior decompression surgery for Chiari I malformation at anywhere from several days to three years prior to being diagnosed with PTC. The diagnosis of PTC was based on temporary symptomatic relief following lumbar puncture which also showed elevated CSF opening pressures. Finally, a VP shunt was placed in each of the 5 patients to relieve the elevated intracranial pressure which resulted in the complete resolution of the patients' symptoms. Discussion: Our study focuses on patients who were diagnosed with and treated for CMI then reported back to the clinic within several days to three years complaining of symptoms of headache. Upon re-presenting to the clinic, a CSF flow study was performed which showed normal flow of CSF. Then, these patients underwent a lumbar puncture which demonstrated an elevated opening pressure (and ICP) and a temporary relief of the headache with lumbar drainage. A VP shunt was placed for each patient to treat for PTC, and the patients' headaches were relieved. Conclusion: This study suggests that the presence of Chiari I malformation in a patient conceals the symptoms of PTC which may become apparent following posterior decompression surgery. Other possibilities could be that the patients are misdiagnosed for Chiari I malformation when they are in fact suffering from PTC, or that PTC is a complication of surgery.